Representasi Peristiwa Sejarah Dalam Puisi Amsterdam-Batavia Karya Zeffry J. Alkatiri - Ira Septiansi; Murdiyah Winarti; Didin Saripudin (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to explore the representation of historical events in the poem Amsterdam-Batavia by Zeffry J. Alkatiri and examine how the poem functions as a medium for reflecting on Dutch colonialism in Indonesia. Within the context of history education, the poem is also considered to have potential as an alternative learning source that can offer students a deeper and more emotional understanding of the past. The research adopts a qualitative approach using Critical Discourse Analysis (CDA) through the Discourse-Historical Approach (DHA) developed by Ruth Wodak. The poem is analyzed through four main stages: identifying discourse topics, conducting linguistic analysis, examining the historical and socio-political context, and integrating findings to reveal power relations, ideologies, and identities embedded in the text. The findings show that Amsterdam-Batavia represents various significant historical events, particularly the spice trade, Dutch maritime expeditions, colonial violence in the Maluku and Banda Islands, and the development of colonial infrastructure in Batavia. The poem also highlights the contrast between the luxury enjoyed by Dutch colonizers and the suffering experienced by both the indigenous population and some Dutch sailors. Through rich symbolism and poetic language, the poet effectively conveys historical meaning in a critical and evocative manner. The study concludes that Amsterdam-Batavia holds not only literary value but also strong historical significance. This poem can serve as an effective teaching material in history education, especially in fostering empathy, contextual understanding, and critical awareness among students regarding colonial legacy and its lasting impact.